Labour Mobility of Migrants and Natives in the European Union: An Empirical Test of the 'Greasing of the Wheels' Effect of Migrants - Michael Landesmann; Sandra M. Leitner (The Vienna Institute for International Economic Studies (wiiw), 2015)
Abstract In the context of current developments of large refugee movements across Europe, it is important to study the impact of migration flows in the European economy. One aspect of this is the impact on mobility patterns (i.e. in and out of jobs, across sectors, across regions and across types of jobs). This paper presents a comprehensive account of key determinants of labour mobility of both migrant and native workers across the EU economies between 2000 and 2011. The main indicators examined are the gross employment reallocation and net employment creation rates (GERR and NECR, respectively) taken over from Davis and Haltiwanger (1992, 1999). We analyse differences in mobility patterns in the EU‑15 and the NMS as regards age groups, skill groups, gender, length of job tenure, and the impact of labour market institutions. A particular focus of the study is the potential of migrants to 'grease the wheels' (Borjas, 2001) of labour markets by either themselves showing higher mobility rates or impacting on the mobility patterns of natives or existing migrants. This impact is analysed in great detail with respect to the differentiated impact of migrants of different skill groups or from different countries of origin on patterns of labour market mobility. Furthermore, apart from overall labour market mobility, we also examine inter-regional and inter-sectoral mobility.
Keywords: F22; J61; J62; J63; R23; 330; labour mobility; employment reallocation; net employment creation; European Union; international migration; inter-sectoral and regional migration